2018
DOI: 10.3928/01484834-20180618-10
|View full text |Cite
|
Sign up to set email alerts
|

Service-Learning: Promoting Empathy Through the Point-in-Time Count of Homeless Populations

Abstract: Health professional programs can use the PIT count to expose students to individuals living in poverty, as well as provide meaningful curricular opportunities to foster a culturally competent and empathetic health services work force. [J Nurs Educ. 2018;57(7):436-439.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Projects reported students interacting with hundreds of clients at a homeless shelter, a mega‐clinic and through a TB outreach program (Belcher & DeForge, 2012; Niemi, Payne, & Bates, 2018; Schoon, Champlin, & Hunt, 2012). Students reported feelings of value and enthusiasm, as well as an improved understanding of challenges faced by communities (Broussard, 2010; Champlin & Kunkel, 2017; Pennington, Coast, & Kroh, 2010; Pierangeli & Lenhart, 2018; Van Doren & Vander Werf, 2012). Suggestions included explicit support of key leaders in community organizations, increased support and training of faculty, increased evaluation of impact, and long‐term follow‐up of students and community outcomes (Dunlap, Marver, Morrow, Green, & Elam, 2011; Gillis & Mac Lellan, 2013; Sandberg, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Projects reported students interacting with hundreds of clients at a homeless shelter, a mega‐clinic and through a TB outreach program (Belcher & DeForge, 2012; Niemi, Payne, & Bates, 2018; Schoon, Champlin, & Hunt, 2012). Students reported feelings of value and enthusiasm, as well as an improved understanding of challenges faced by communities (Broussard, 2010; Champlin & Kunkel, 2017; Pennington, Coast, & Kroh, 2010; Pierangeli & Lenhart, 2018; Van Doren & Vander Werf, 2012). Suggestions included explicit support of key leaders in community organizations, increased support and training of faculty, increased evaluation of impact, and long‐term follow‐up of students and community outcomes (Dunlap, Marver, Morrow, Green, & Elam, 2011; Gillis & Mac Lellan, 2013; Sandberg, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were seen in another study conducted by Pierangeli et al which involved nursing and public health students participating in a point-in-time count of unsheltered homeless. The results demonstrated that students showed increased levels of empathy towards the homeless through a better understanding of the social determinants of health as well as a greater appreciation for the individual experiences of the homeless (Pierangeli and Lenhart, 2018). While this research demonstrates that interaction with the homeless can significantly impact empathetic attitudes, it also highlights the opportunity to examine if these results are generalisable to the Australian paramedic profession.…”
Section: Introductionmentioning
confidence: 77%
“…We also found that including students provided a feasible and excellent hands-on project for courses on research methods in social work and the social sciences in universities and community colleges with large percentages of local students embedded in the region. The use of local student populations enrolled in research classes to collaborate with local homeless coalitions to carry out homeless census is replicable elsewhere and has been done in the past (Hatchett 2004, Lin et al 2017; Pierangeli and Lenhart 2018). Adding an emphasis on the marginally housed produced a better count of the homeless population in El Paso.…”
Section: Resultsmentioning
confidence: 99%